Ion neutralization and high-energy electron emission in He+ scattering by a highly oriented pyrolitic graphite surface - Iglesias Garcia, Adalberto de Jesus (2014)
We report results of ion neutralization of low-energy positive He ions interacting with a surface of highly oriented pyrolitic graphite as a function of the impinging energy. We found a neutralization probability close to unity for a wide energy range. This behavior is reproduced by our theory only if we take into account the electronic correlation introduced by the He first excited states considered as possible neutralization channels. The finite occupation of these excited states opens the Auger deexcitation process as a source of emitted electrons. The calculation of this electron emitted spectrum is complex as it requires the knowledge of the energies and occupations of the atomic configurations as a function of the ion trajectory. Our calculation shows the presence of high energetic secondary electrons contributing to the Auger electron emission spectra of this system.